Characterization of Xylanase from microbulbifer SP. Cl37 for industrial applications - Mah, Ming Hui, 1994-, author 611584; Chong, Chun Shiong, supervisor 421074; Fakulti Sains 8004 (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2019)
Thesis (Sarjana Sains, Pengkhususan : Sains Forensik) - Universiti Teknologi Malaysia, 2019